2006
DOI: 10.1590/s0100-204x2006000200022
|View full text |Cite
|
Sign up to set email alerts
|

Funcionalidade da oleoresina de páprica microencapsulada em goma-arábica e amido de arroz/gelatina

Abstract: Resumo -O objetivo deste trabalho foi avaliar a funcionalidade da oleoresina de páprica microencapsulada em goma-arábica e amido de arroz/gelatina, incorporada nos sistemas-modelo bolo e gel de gelatina. Avaliou-se a cor por meio de medida instrumental e aceitação sensorial por atributos de aparência e aceitação global. O pigmento encapsulado solubilizou-se, tingiu e se distribuiu uniformemente nos bolos, os quais apresentaram boa aceitação global. Nos géis, a goma apresentou desempenho superior ao amido/gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…To prepare each sample of cake, 0.31 g of encapsulated carotene/250 g of cake batter was used before baking (Santos et al . ; Rocha et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…To prepare each sample of cake, 0.31 g of encapsulated carotene/250 g of cake batter was used before baking (Santos et al . ; Rocha et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the supplementation of antioxidants, microencapsulation is also recognized as a promising way of stabilizing natural colorants . Spray‐draying is the most widely used microencapsulation technology in the food industry and has been reported to effectively protect paprika oleoresin from oxidation . Furthermore, Santos et al evaluated the functionalities of microencapsulated paprika oleoresin in Arabic gum and rice starch/gelatin incorporated into cake and gelatin gel.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Santos et al evaluated the functionalities of microencapsulated paprika oleoresin in Arabic gum and rice starch/gelatin incorporated into cake and gelatin gel. It was found that the encapsulated pigment successfully dyed the cakes without negative effect on taste, flavor or texture of analyzed systems, but reduced the global sensory acceptance of gelatin gel . To overcome the adverse effects of high temperature used in spray‐drying, Zilberboim et al .…”
Section: Introductionmentioning
confidence: 99%
“…Paprika oleoresins are used in the food industry. The properties of encapsulated paprika oleoresin in rice starch/gelatin and Arabic gum were evaluated by Santos et al in food applications, with a satisfying effect without affecting its texture, taste or flavor [48].…”
Section: Paprikamentioning
confidence: 99%